Researching the Future in Information Systems IFIP WG 8.2 Working Conference, Turku, Finland, June 6-8, 2011. Proceedings - Chiasson, Mike.; Henfridsson, Ola.; Karsten, Helena; DeGross, Janice I.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the IFIP WG 8.2 Working Conference "Researching the Future", Future IS 2011, held in Turku, Finland, in June 2011. The 17 revised full papers presented together with 4 panels and workshops were carefully reviewed and selected from numerous submissions. The papers are organized into 6 topical sections: how the future and the past are connected and inter-related; critical view of the future; technological futures; the future of information technology and work-related practices in health care; the future of industrial and institutional practices and outcomes through information technology; and the future of critical realism in IS research.
Keywords: Computer science; Computer Communication Networks; Information systems; Information Systems; Computer Science; Management of Computing and Information Systems; Computers and Society; Information Systems Applications (incl.Internet).; User Interfaces and Human Computer Interaction; Computation by Abstract Devices; Computer Communication Networks